Diet of mid-Atlantic Sowerby’s beaked whales Mesoplodon bidens - Pereira, José N. (2011)
The first mid-Atlantic diet of Mesoplodon beaked whales is presented, from ten Sowerby's Mesoplodon bidens stranded in the Azores region between 2002 and 2009. This doubles the worldwide number of stomachs sampled, and reveals new feeding habits for this species. The mean number of prey items per stomach was 85±89 (range: 12–238), with fish accounting for 99.3% and cephalopods contributing less than 1% of total prey. Fish otoliths from 15 families and cephalopod lower mandibles from three families were identified, representing 22 taxa. The diet consisted mainly of small mid-water fish, the most numerous being Diaphus sp., Lampanyctus sp. and Melamphaidae species. Myctophids were present in all stranded individuals, followed by Diretmidae, Melamphaidae and Opisthoproctus soleatus, while the remaining fish species were scarce or single occurrences. Consistency of diet in four different years reveals a divergence from all previous records in continental areas, where mainly neritic and shelf-break benthopelagic fish species have been reported. Mid-Atlantic Sowerby's beaked whales' showed dietary plasticity, feeding on the most abundant mid-water groups occurring between 0 and750 m. Trophic level from prey numerical frequency was estimated at 4.4±0.46.